Dynamic inverse controller with Matrix Converter Drive Feed Three Phase Induction Motor - Keream S.S.; Abdalla A.N.; Daud M.R.B.; Koh J. (EDP Sciences, 2023)
Controllers; Electric drives; Induction motors; Inverse problems; Matrix algebra; Matrix converters; Experimental modeling; Induction motor drive; Input voltage sources; Matrix converter drives; Modulation techniques; Nonlinear dynamic inverse; Three phase induction motor; Torque ripple minimization; Electric machine control